2018
DOI: 10.3168/jds.2017-13327
|View full text |Cite
|
Sign up to set email alerts
|

Effects of supplementation with ruminally protected choline on performance of multiparous Holstein cows did not depend upon prepartum caloric intake

Abstract: Objectives were to evaluate the effect of prepartum energy intake on performance of dairy cows supplemented with or without ruminally protected choline (RPC; 0 or 17.3 g/d of choline chloride; 0 or 60 g/d of ReaShure, Balchem Corp., New Hampton, NY). At 47 ± 6 d before the expected calving date, 93 multiparous Holstein cows were assigned randomly to 1 of 4 dietary treatments in a 2 × 2 factorial arrangement. Cows were fed energy to excess [EXE; 1.63 Mcal of net energy for lactation/kg of dry matter (DM)] or to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
88
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(100 citation statements)
references
References 62 publications
7
88
4
Order By: Relevance
“…Data from 2 independent experiments conducted at the University of Florida were combined (Zenobi et al, 2018a;Bollatti et al, 2020a,b) into a single file for analyses. Details of cows, housing, diets, and general management are presented in the respective manuscripts.…”
Section: Methodsmentioning
confidence: 99%
“…Data from 2 independent experiments conducted at the University of Florida were combined (Zenobi et al, 2018a;Bollatti et al, 2020a,b) into a single file for analyses. Details of cows, housing, diets, and general management are presented in the respective manuscripts.…”
Section: Methodsmentioning
confidence: 99%
“…Previous work with dairy cows has demonstrated a positive effect of Met supply during the periparturient period on health and production performance, including alleviation of inflammation and oxidative stress (Osorio et al, 2014b;Sun et al, 2016;Zhou et al, 2016aZhou et al, ,b, 2017Batistel et al, 2017Batistel et al, , 2018. In some, but not all (Zhou et al, 2016a,c;Zenobi et al, 2018), studies with rumen-protected Chol, lactation performance and antioxidant capacity and immune function of dairy cows has been improved (Zom et al, 2011;Lima et al, 2012;Sun et al, 2016). Although gene expression and enzyme activity data suggested that Chol supplementation did not alter Met synthesis (Zhou et al, 2017), a better assessment of underlying mechanisms is challenging to address in vivo.…”
Section: One-carbon Metabolismmentioning
confidence: 99%
“…The regulation and coordination of lipid metabolism (at molecular, enzyme, and metabolite level) among adipose tissue, liver, gut, and mammary gland are key components of the adaptations to lactation . Although several recent studies have enhanced the mechanistic understanding of the role of Met and Chol in the context of the physiology of the periparturient cow (Zhou et al, 2016a(Zhou et al, ,b, 2017Zenobi et al, 2018), studying mechanistic aspects of Met and Chol metabolism in liver in vivo becomes challenging.…”
Section: Introductionmentioning
confidence: 99%
“…Liver lipid infiltration develops in peripartal dairy cows fed diets containing inadequate or adequate Met (Zhou et al, 2016b;Zenobi et al, 2018). A potential approach to mitigate fatty liver is dietary methyl donor supplementation (MDS).…”
mentioning
confidence: 99%
“…Choline and Met are methyl donors that have received attention. Supplementation of rumen-protected (RP) choline chloride (11.7 to 14.4 g/d of choline ion) has been shown to increase serum total TAG (Guretzky et al, 2006) and decrease liver total TAG concentrations (Zom et al, 2011); however, these findings were not observed by others (Zahra et al, 2006;Zhou et al, 2016b;Zenobi et al, 2018). The abilities of RP-Met (Met at 0.07 to 0.10% ration DM) to mitigate hepatic lipid accrual are also inconsistent.…”
mentioning
confidence: 99%